2021
DOI: 10.1088/1755-1315/648/1/012143
|View full text |Cite
|
Sign up to set email alerts
|

The ability of some microbes to solubilize the hardly soluble phosphorous and potassium from various sources in vitro

Abstract: Utilization of bio-fertilizer is an alternative option to maintain the available phosphorus (P) and potassium (K) in the soil. To develop such a bio-fertilizer, the ability of microbes to solubilize phosphate and potassium is one of the most important things. A set of experiments was conducted to evaluate the ability of some microbes (7 bacteria and 7 fungi isolates) to solubilize the hardly soluble P (Ca3PO4, AlPO4, FePO4 and Blora rock phosphate) and K (Malang feldspar) sources in vitro. The results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Some PSM showing larger holozones did not lower the pH significantly. Flatian, Anas & Sutandi (2021) described that proton excretion with ammonium ion assimilation is the most effective description for microbial solubilization under low acid production.…”
Section: Discussionmentioning
confidence: 99%
“…Some PSM showing larger holozones did not lower the pH significantly. Flatian, Anas & Sutandi (2021) described that proton excretion with ammonium ion assimilation is the most effective description for microbial solubilization under low acid production.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that not having the stress generated by the macronutrient deficit, it did not activate the microbial mechanisms that allow the solubilization of the minerals present in the rocks, reducing their activity to the consumption of the available P and K. In the studies carried out by Osorno Bedoya and Osorio Vega (2017) was evidenced that a higher concentration of soluble P at the beginning of the process decreased the solubilization of phosphate rock by Mortierella sp. while in results reported by Flatian et al (2021), despite presenting initial KS, found solubilization of feldspar by unidentified bacteria and fungi.…”
Section: Discussionmentioning
confidence: 74%
“…Pearson correlation between pH, organic acids and phosphate solubilizing potential of efficient bacterial isolates i.e., Pseudomonas songnenensis (GR3) and Stutzerimonas stutzeri (HH2) indicated that pH, phosphate solubilization efficiency and acid production ability of the bacterial strains is significantly positively correlated. However, for the bacterial isolate HH2 phosphate solubilization is not directly corelated with pH changes as slight pH change was observed but the change in pH is positively corelated with acid production as noted by Flatian et al (2021) some bacterial isolates did not significantly drop the pH of broth medium in spite of having high phosphate solubilizing ability this may be due to they have adopted different strategy to release bounded phosphate vis releasing proton for ion assimilation. Phosphate solubilization is positively correlated with its highest production of gluconic acid as reported by Hii et al (2020).…”
Section: Discussionmentioning
confidence: 92%